2019
DOI: 10.18203/2349-2902.isj20194421
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparative study between omentopexy and omental plugging in treatment of duodenal perforation

Abstract: Background: Perforation due to duodenal ulcer is a common cause of peritonitis and is considered as one of the most catastrophic complication of duodenal ulcer perforation. Repair of perforation are considered particularly hazardous because of the extensive duodenal tissue loss, friability of the ulcer margins, surrounding tissue inflammation, poor general condition of the patient and overwhelming sepsis due to bacterial peritonitis. Thus, there is a need to compare closure of duodenal perforations by either G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These findings correspond with the results of several previous studies. 19 , 21 , 31 Another study reported that respiratory tract and wound infections were the most common postoperative problems, occurring in > 24% of patients. 32 …”
Section: Discussionmentioning
confidence: 99%
“…These findings correspond with the results of several previous studies. 19 , 21 , 31 Another study reported that respiratory tract and wound infections were the most common postoperative problems, occurring in > 24% of patients. 32 …”
Section: Discussionmentioning
confidence: 99%